2023
DOI: 10.1002/hlca.202200159
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Te‐Containing Recognition Modules for Chalcogen Bonding: Towards Supramolecular Polymeric Materials

Abstract: Aiming at the preparation of one-dimensional (1D) chalcogen-bonded supramolecular polymers at the solid state, this work describes the different syntheses which have been challenged to obtain ditopic molecular modules. At first, tellurazolopyridyl (TZP) rings have been chosen as recognition units, given their well-proven ability and persistency to self-assemble through double Te•••N chalcogen bonds (ChBs). The second synthetic strategy dealt with the preparation of pyridyl-modified ebselen Te-containing analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…If one excludes the use of cationic heterocycles, one can note that outside a crystalline environment, the formation of such dimers is unprecedented. Indeed, even in solution, conclusive data demonstrating such self-assembly of neutral heterocycles have yet to be reported thus far. , Building on earlier studies at the solid state, in which we have shown that chalcogenazolo pyridine (CGP) moieties persistently undergo self-assembly into dimers through double Ch···N interactions, we conjectured that the Se- and Te-bearing CGP motifs could also be exploited to govern molecular assemblies on surfaces (Figure e) . With this aim, we designed and prepared pyrene-based CGP modules that could undergo dimerization through ChB-driven molecular recognition.…”
Section: Introductionmentioning
confidence: 98%
“…If one excludes the use of cationic heterocycles, one can note that outside a crystalline environment, the formation of such dimers is unprecedented. Indeed, even in solution, conclusive data demonstrating such self-assembly of neutral heterocycles have yet to be reported thus far. , Building on earlier studies at the solid state, in which we have shown that chalcogenazolo pyridine (CGP) moieties persistently undergo self-assembly into dimers through double Ch···N interactions, we conjectured that the Se- and Te-bearing CGP motifs could also be exploited to govern molecular assemblies on surfaces (Figure e) . With this aim, we designed and prepared pyrene-based CGP modules that could undergo dimerization through ChB-driven molecular recognition.…”
Section: Introductionmentioning
confidence: 98%